Charge state stabilization of shallow nitrogen vacancy centers in diamond by oxygen surface modification. (23rd March 2017) - Yamano, Hayate; Kawai, Sora; Kato, Kanami; Kageura, Taisuke; Inaba, Masafumi; Okada, Takuma; Higashimata, Itaru; Haruyama, Moriyoshi; Tanii, Takashi; Yamada, Keisuke; Onoda, Shinobu; Kada, Wataru; et al.
Abstract: We investigated the charge state stability and coherence properties of near-surface single nitrogen vacancy (NV) centers in 12 C-enriched diamond for potential use in nanoscale magnetic field sensing applications. The stability of charge states in negatively charged NV centers (NV − ) was evaluated using one of the pulsed optically detected magnetic resonance measurements, Rabi oscillation measurements. During the accumulation of Rabi oscillations, an unstable shallow NV − was converted to a neutral state. As a result, the contrast of Rabi oscillations degraded, depending on charge state stability. We stabilized the NV − state of very shallow NV centers (∼2.6 ± 1.1 nm from the surface) created by 1.2 keV nitrogen ion implantation by diamond surface modification, UV/ozone exposure, and oxygen annealing. This improvement indicates that we can suppress the upward surface band bending and surface potential fluctuations through Fermi level pinning originating from oxygen-terminated diamond surfaces.